Disminución de tiempos operacionales en pozos del Campo Akacias por medio de la implementación de la metodología de la energía mecánica especifica (MSE) (2024)
When drilling an oil well, it is essential to have appropriate drilling parameters to achieve an efficient reduction in drilling times. This directly contributes to the decrease in associated operating costs, as proper optimization of these parameters can increase the overall efficiency of the drilling process, improve productivity and minimize downtime, resulting in a more profitable operation. In this sense, the objective of the project has focused on improving drilling efficiency through the construction and evaluation of a parameter map that is based on the analysis of the rate of penetration (ROP), implementing the calculation of the specific mechanical energy (MSE). In the initial stages, a methodology was designed and applied that considered key factors such as weight on bit (WOB), torque (T), revolutions per minute (RPM) and rate of penetration (ROP). Additionally, specific adjustments were implemented, such as the adjustment factor based on wellbore angle.